THE MOTIVATIONAL MECHANISM OF EFFECTIVE USE OF HUMAN RESOURCES - Yusupov, Abbosxon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
Effective management of human resources provides any organization with advantages such as competitive superiority, optimization of production or service processes, and the overall achievement of success. The article highlights the impact of motivation on the effective use of human resources. Classical theories of motivation have been analyzed. During the analysis process, various literature sources were reviewed, and relevant conclusions and recommendations were developed.